2023
DOI: 10.1002/pi.6497
|View full text |Cite
|
Sign up to set email alerts
|

On the injection molding of thick‐walled thermoplastic vulcanizates: linking static and dynamic mechanical properties with morphology

Abstract: Elastomers are widely used in the automotive industry in anti‐vibration components. Commonly, elastomeric anti‐vibration components are made of thermoset rubbers. However, new drivers related to the requirements of the new sustainable mobility industry are pushing towards the substitution of thermoset rubbers by thermoplastic elastomers. Among thermoplastic elastomers, thermoplastic vulcanizates (TPVs) represent an interesting material choice for anti‐vibration products due to their light weight, recyclability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, processing parameters influence the particles' distortion state, as shown in Reference 3. In a recent publication by Burgoa et al, 12 the anisotropic nature of injection molded TPV has been confirmed.…”
Section: Introductionmentioning
confidence: 88%
“…Nevertheless, processing parameters influence the particles' distortion state, as shown in Reference 3. In a recent publication by Burgoa et al, 12 the anisotropic nature of injection molded TPV has been confirmed.…”
Section: Introductionmentioning
confidence: 88%